EKSTRAKSI FLAVONOID DARI BAYAM MERAH (Alternanthera Amoena Voss) - Salwa Jody Gustia; Irsa Septiawan; Iriany Iskandinata (JURNAL INTEGRASI PROSES, 2017)
Red spinach (Alternanthera Amoena Voss) contains antioxidant compounds such as betalain, karatenoid, vitamin C and flavonoids. Antioxidant compounds serve to neutralize free radicals in the body, so that the body is protected from degenerative diseases. The separation of flavonoid compounds from red spinach is carried out by using extraction process. This study aims to obtain mass transfer coefficient (Kc) in red spinach extraction process and study the relationship between agitation speed with mass transfer coefficient, and antioxidant activity of the flavonoids  obtained. The relationship of Kc and agitation speed is expressed in an equation of Sherwood Number (Sh). Red spinach that had been cut to the square sized (1 x 1 cm) was extracted by using aquadest in an agitated vessel at a temperature of 60oC and agitation speed of 100 rpm, 200 rpm and 300 rpm. Every 5 minutes sample was taken and its total flavonoid was measured using a UV-VIS spectrophotometer at 415 nm. The extraction process terminated after the equilibrium condition had been reached. The conclusion obtained from this study is the value of Kc increases along with the increasing of agitation speed and equation of sherwood number (Sh) for this extraction is Sh = 240,6154Re 0,6195.